The New Kinship : Constructing Donor-Conceived Families - Cahn, Naomi R. (Book collections on Project MUSE., 2013)
No federal law in the United States requires that egg or sperm donors or recipients exchange any information with the offspring that result from the donation. Donors typically enter into contracts with fertility clinics or sperm banks which promise them anonymity. The parents may know the donor's hair color, height, IQ, college, and profession; they may even have heard the donor's voice. But they don't know the donor's name, medical history, or other information that might play a key role in a child's development. And, until recently, donor-conceived offspring typically didn't know that one of.